Structural insights into the main S-layer unit of Deinococcus radiodurans reveal a massive protein complex with porin-like features - Farci, Domenica; Aksoyoglu, Mehmet Alphan; Farci, Stefano Francesco; Bafna, Jayesh Arun; Bodrenko, Igor; Ceccarelli, Matteo; Kirkpatrick, Joanna; Winterhalter, Mathias; Kereïche, Sami; Piano, Dario (The Journal of biological chemistry, 2020)
In the extremophile bacterium Deinococcus radiodurans, the outermost surface layer is tightly connected with the rest of the cell wall. This integrated organization provides a compact structure that shields the bacterium against environmental stresses. The fundamental unit of this surface layer (S-layer) is the S-layer deinoxanthin-binding complex (SDBC), which binds the carotenoid deinoxanthin and provides both, thermostability and UV radiation resistance. However, the structural organization of the SDBC awaits elucidation. Here, we report the isolation of the SDBC with a gentle procedure consisting of lysozyme treatment and solubilization with the nonionic detergent n-dodecyl-β-d-maltoside, which preserved both hydrophilic and hydrophobic components of the SDBC and allows the retention of several minor subunits. As observed by low-resolution single-particle analysis, we show that the complex possesses a porin-like structural organization, but is larger than other known porins. We also noted that the main SDBC component, the protein DR_2577, shares regions of similarity with known porins. Moreover, results from electrophysiological assays with membrane-reconstituted SDBC disclosed that it is a nonselective channel that has some peculiar gating properties, but also exhibits behavior typically observed in pore-forming proteins, such as porins and ionic transporters. The functional properties of this system and its porin-like organization provide information critical for understanding ion permeability through the outer cell surface of S-layer-carrying bacterial species.
Keywords: Protein Binding; electrophysiology; multiproteinové komplexy; protein structure; Bacterial Proteins; electron microscopy (EM); Deinococcus; membránové glykoproteiny; S-layer; poriny; membrane protein; S-layer deinoxanthin–binding complex (SDBC); porin-like complex; Deinococcus radiodurans; vazba proteinů; Cell Membrane; gating; buněčná stěna; Cell Wall; Carotenoids; Porins; mass spectrometry (MS); Membrane Glycoproteins; buněčná membrána; stress resistance; bakteriální proteiny; structure–function; Multiprotein Complexes; karotenoidy